2018
DOI: 10.21548/39-1-2467
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Grape Temperature at Pressing on Organic Acids and Oenological Characteristics of Méthode Cap Classique Wines

Abstract: Maintaining the chemical composition of a wine is essential for the wine industry. Although the sugar-acid balance of a wine is of primary sensory importance, individual acids and oenological variables are equally important. The main focus of this study was to investigate the impact of grape temperature at harvest on the volatile acidity (VA), titratable acidity (TA), pH and alcohol levels, and the organic acid (citric, malic, pyruvic and succinic) characteristics of Méthode Cap Classique (MCC) wines produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…The wine fermentation contributes to the transformation, disappearance, or appearance of different acids [130]. Chidi et al [131] studied the influence of temperature at pressing on organic acids and concluded that Chardonnay base wines were richer in malic and succinic acids, whereas Pinot noir wines were characterized by higher levels of malic, citric, and pyruvic acids. In addition, pyruvic acid was only detected after the secondary fermentations in wines from both regions.…”
Section: Organic Acidsmentioning
confidence: 99%
“…The wine fermentation contributes to the transformation, disappearance, or appearance of different acids [130]. Chidi et al [131] studied the influence of temperature at pressing on organic acids and concluded that Chardonnay base wines were richer in malic and succinic acids, whereas Pinot noir wines were characterized by higher levels of malic, citric, and pyruvic acids. In addition, pyruvic acid was only detected after the secondary fermentations in wines from both regions.…”
Section: Organic Acidsmentioning
confidence: 99%